African Traditional Religion in South Africa: An Annotated Bibliography - Chidester, David; Kwenda, Chirevo; Petty, Robert; Tobler, Judy; Wratten, Darrel (Greenwood Press, 1997)
In a changing South Africa, recovering the meaning and power of African tradition is a matter of crucial importance. This work participates in that recovery by providing a comprehensive guide to research on the indigenous religious heritage of this dynamic country. Detailed reviews of over 600 books, articles, and theses are offered along with introductory essays and detailed annotations that define the field of study. This work plus two forthcoming volumes, Christianity in South Africa: An Annotated Bibliography and Islam, Hinduism, and Judaism in South Africa: An Annotated Bibliography will become the standard reference work on South African religions. Scholars and students in Religious Studies, Social Anthropology, History, and African Studies will find this set particularly useful.This work organizes and annotates all the relevant literature on Khoisan, Xhosa, Zulu, Sotho-Tswana, Swazi, Tsonga, and Venda traditions. The annotations are concise yet detailed essays written in an engaging and accessible style and supported by an exhaustive index, which comprise a full and complex profile of African traditional religion in South Africa.
Keywords: Religion / Comparative Religion; Religion / General